Pengembangan LKPD Materi Segitiga Berbasis PBL Kelas VII Di SMP Pesantren Raudlotul Ulum - Ramadhani Valiani; Anggita Oktaviana Putri (FKIP Universitas Mataram, 2026)
This study aims to develop Student Worksheets (LKPD) on the subject of perimeter and area of triangles for seventh-grade students at Raudlotul Ulum Islamic Boarding School Junior High School, with a focus on problem solving. The method used is development research with a 4-D model, which includes the stages of needs analysis, design, and development, while the dissemination stage is not carried out because the research focuses on limited trials. Research data were obtained through learning observations, interviews with teachers and students, and questionnaires on student responses to the developed LKPD. The results of the needs analysis showed that mathematics learning was still dominated by the lecture method, student involvement was relatively low, and there were no teaching materials available to facilitate systematic problem solving. In the design and development stage, the worksheets were compiled by presenting contextual problems as the starting point for learning and supplemented with structured steps for solving them. Limited trials with ten students showed that the worksheets had clear language, visual appeal, appropriate material, and were useful as supporting teaching materials. Based on these findings, the developed LKPD is declared suitable for use as an alternative teaching material to help students understand the concepts of perimeter and area of a triangle through the problem-solving process.